2015
DOI: 10.1097/mao.0000000000000834
|View full text |Cite
|
Sign up to set email alerts
|

Dose Effect of Intratympanic Dexamethasone for Idiopathic Sudden Sensorineural Hearing Loss

Abstract: To our knowledge, this is the first demonstration of superiority of IT DEX at 24 mg/mL for the treatment of ISSNHL, with significantly better recovery of PTA. Our data suggest that treatment should be initiated as soon as possible. A prospective randomized trial to confirm the optimal dose is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 32 publications
3
32
0
1
Order By: Relevance
“…larger change in PTA with earlier onset of treatment (figure 5a). This is in correspondence with arguments often used in communication of doctors with patients when they suggest to start a therapy as soon as possible to get the greatest benefit from the treatment (3942). However, such an argument appears not to be supported by the present data.…”
Section: Discussionsupporting
confidence: 68%
“…larger change in PTA with earlier onset of treatment (figure 5a). This is in correspondence with arguments often used in communication of doctors with patients when they suggest to start a therapy as soon as possible to get the greatest benefit from the treatment (3942). However, such an argument appears not to be supported by the present data.…”
Section: Discussionsupporting
confidence: 68%
“…Among the factors that could influence hearing outcome, time from onset of HL to the baseline visit was found to be statistically significant (p=0.030). Our study confirms other reports that delaying treatment has negative influence on hearing improvement [2,17] . Other factors, such as age, presence of tinnitus or vertigo, did not impact the hearing threshold in our study.…”
Section: Discussionsupporting
confidence: 82%
“…The concentration used in treatment is often associated with availability and approval of each country or medical center and ranged from 4 mg/mL to 24 mg/mL for DEX. A higher concentration was found to be more effective [17] . The number of applications from single injection to four injections over several days has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of IT steroids are attributed to a higher perilymph steroid level. Dosing regimens vary from study to study, and higher concentration per dose has also been shown to be efficacious …”
Section: Introductionmentioning
confidence: 99%